Pathomorphological characteristics of the restructuring of acinar-insular tissue with severe fibrosis of the pancreas in patients with chronic pancreatitis - V.А. Tumanskiy; I.S. Kovalenko (Patologìâ)
Pathomorphological analysis of acinar-insular restructuring of the pancreas in 20 patients with chronic pancreatitis showed that in severe peri-intralobular fi brosis in areas of active restructuring of acinar tissue increases apoptosis of caspase-3+ acinar cells, partially compensated by their proliferation and the formation of new small CA 19-9-positive terminal ducts. On the background of signifi cant level of MMP-9 expression and a very mild level of TIMP-1 expression by pancreatic cells the ordered molecular fi brous matrix of the basement membranes of acini is replaced by fi brillar collagen types I and III, excluding the possibility of regeneration of typical acini. The loss of acinar tissue progresses in severe fi brosis and then it is substituted by functionally invalid tubular complexes and tubularinsular complexes with functioning islet endocrine islets of Langerhans.